The role of α2-macroglobulin in endogenous uveitis in children - L. A. Katargina; N. B. Chesnokova; E. V. Denisova; M. A. Khrabrova; O. V. Beznos (Российский офтальмологический журнал, 2023)
Purpose: to analyze the activity of α2-macroglobulin (α2-MG) in the tear, blood serum (BS), and aqueous humour (AH) in children with uveitis, and to assess the possibility of using α2-MG for inflammation activity estimation and prognosis.Material and methods. 76 children with uveitis (135 eyes) aged 3 to 17 (ave. 10.45 ± 3.34 years), were tested for the activity of α2-MG (300 tear samples, 154 BS samples, 39 AH samples). The dynamics of α2-MG was assessed in the tear of 56 patients, and in BS of 53 patients. α2-MG activity was determined by the enzymatic method using the specific substrate N-benzoyl-DL-arginine-p-nitroanilide (BAPNA). The optical density was measured using a multifunctional photometer for Synergy MX microplates (BioTek, USA).Results. No correlation was found between the α2-MG activity and the inflammation activity and localization of uveitis. In contrast, a significant decrease in α2-MG activity was found in the tear after anti-inflammatory therapy (p = 0.013). Also, a significant preoperative α2-MG increase was noted in the tear of children who experienced fibrin effusion into the anterior chamber of the eye in the early postoperative period (p = 0.022) It was shown that α2-MG activity in BS drops significantly as the patients grow up (p = 0.025). As the degree of proliferation increases, the activity of α2-MG in AH also increases (p = 0.049).Conclusion. An increase of α2-MG activity in the tears in the preoperative period may be important for the prognosis of fibrin formation in the anterior chamber during the postoperative period. α2-MG in the tear is highly sensitive to anti-inflammatory drugs, which reduce its activity. In BS the highest activity of α2-MG was revealed at the age of 3–6 years, whereupon it is decreasing. In AH, the activity of α2-MG correlates with the stage of the proliferative process.